PROSES PENUNTUTAN TERHADAP PEMENUHAN RESTITUSI BAGI KORBAN ANAK PELECEHAN SEKSUAL - Kholim, Fellicia Angelica; Firmansyah, Hery (Universitas Muhammadiyah Ponorogo, 2024)
The existence of the Republic of Indonesia Attorney General's Law to oversee the role of public prosecutors in overseeing the fulfillment of restitution for children as victims. Also, the existence of Government Regulation of the Republic of Indonesia Number 43 of 2017 concerning the Implementation of Restitution for Children Who Are Victims of Criminal Acts in ensuring the overall implementation of restitution. This is important to conduct a study because there are problems in its implementation, such as the lack of knowledge of victims regarding their rights to obtain restitution as a form of recovery for the suffering they have experienced. This study uses a normative research method with the approach used being the statute approach with the data sources used being secondary data in the form of primary legal materials, secondary legal materials, and non-legal legal materials. The results of the study show the manifestation of restitution for child victims, there is an institution called the Witness and Victim Protection Agency (LPSK) which explains that there are 3 (three) types of compensation obtained for victims, namely Article 7A of Law Number 31 of 2014 concerning Witness and Victim Protection contains compensation for loss of wealth, compensation for suffering as a result of criminal acts, and/or reimbursement of medical and/or psychological care costs. The role of the public prosecutor in overseeing the prosecution process for the fulfillment of restitution in cases of child sexual abuse is very important to achieve comprehensive justice for the victim. The public prosecutor has an important role in handling cases of child sexual abuse by ensuring that the perpetrator receives an appropriate punishment in order to provide a deterrent effect.